GENETIC VARIABILITY AND DIVERGENCE STUDIES FOR YIELD AND ITS RELATED TRAITS IN SUNFLOWER - B.V. RAVI PRAKASH REDDY; Y. PRUDHVI KUMAR REDDY; K. VENKATARAMANAMMA (The Journal of Research ANGRAU, 2025)
The development and cultivation of hybrids is the key to improving the productivity of  sunflower crop. The present study evaluated 52 hybrids during Rabi 2023-24 for genetic parameters  and genetic variability in relation to yield and its attributing traits. Among the experimental hybrids,  the analysis of variance revealed significant differences in yield and its attributes. The traits seed yield (kg ha-1) and oil yield (kg ha-1) recorded the high GCV (26.5 and 27.8) and PCV (28.2 and 29.9) values, respectively. The traits seed yield (kg ha-1), hundred seed weight and oil yield (kg ha 1) recorded the high heritability (>60%) along with high genetic advance expressed as a percentage  of mean (>20%). Accordingly, additive genetic effects play a major role in theinheritance of these  traits with little influence from the environment.The assessment of genetic diversity grouped the  52 hybrids into six distinct clusters, with the majority (34 hybrids) falling into Cluster I. Among the  clusters, the maximum intra-cluster distance was observed in Cluster II (12.14). The greatest inter-cluster distance (75.18) was observed between Cluster VI and Cluster II, suggesting that  interbreeding among members in these two clusters could facilitate the production of highly  desirable transgressive segregants. Based on a genetic divergence study, the hybrids SH 2876,  SH 2883, SH 2896, SH 2904, SH 2895, SH 2878, SH 2886, SH 2899, SH 2884, SH 2922 and KBSH 78 were utilized in the sunflower inbred line development programme